2014
DOI: 10.1007/s13197-014-1506-4
|View full text |Cite
|
Sign up to set email alerts
|

Microencapsulation of Lactobacillus plantarum MTCC 5422 in fructooligosaccharide and whey protein wall systems and its impact on noodle quality

Abstract: Noodles are staple cereal food in many countries; however addition of encapsulated probiotics into noodle formulation, its effect on noodle quality and cell viability has not yet been reported. The aim of this study was to prepare microencapsulated Lactobacillus plantarum (MTCC 5422) by freeze drying with wall material combinations such as fructooligosaccharide (FOS), FOS +whey protein isolate (WPI), and FOS+denatured whey protein isolate (DWPI) to evaluate best wall system. Results showed that FOS+DWPI wall s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(24 citation statements)
references
References 38 publications
3
20
0
Order By: Relevance
“…The different methods for the microencapsulation of probiotic microorganisms involved several physical and chemical principles. Successful methods used in the microencapsulation of probiotics include: spray drying [21,22]; spray chilling (also called spray cooling or congealing) [23,24]; spray freeze drying [25,26]; lyophilisation [27,28]; electrospraying [29,30]; layer-by-layer [31,32]; fluidised bed drying [33,34]; extrusion [35,36] and its improved version: the vibrating nozzle technology [37,38]. Emulsification [39,40] and coacervation [41,42] are other important and often used physicochemical techniques.…”
Section: Methods For Microencapsulation Of Probioticsmentioning
confidence: 99%
See 1 more Smart Citation
“…The different methods for the microencapsulation of probiotic microorganisms involved several physical and chemical principles. Successful methods used in the microencapsulation of probiotics include: spray drying [21,22]; spray chilling (also called spray cooling or congealing) [23,24]; spray freeze drying [25,26]; lyophilisation [27,28]; electrospraying [29,30]; layer-by-layer [31,32]; fluidised bed drying [33,34]; extrusion [35,36] and its improved version: the vibrating nozzle technology [37,38]. Emulsification [39,40] and coacervation [41,42] are other important and often used physicochemical techniques.…”
Section: Methods For Microencapsulation Of Probioticsmentioning
confidence: 99%
“…Moreover, these small peptides also exhibited the capacity to prevent enteropathogenic Escherichia coli, Salmonella typhimurium, and Shigella flexneri from adhering to intestinal cells [172,173]. Whey proteins, in its different forms, were recently explored as coating materials for the microencapsulation of probiotics [28,30,41,58,72,95,97,[102][103][104][105].…”
Section: Proteinsmentioning
confidence: 99%
“…bCyclodextrin as encapsulating agent protects the core material, against degradation due to temperature and pH (Kalogeropoulos, Yannakopoulou, Gioxari, Chiou, & Makris, 2010). The incorporation of microencapsulated bioactive compound into foods enables the development of new functional foods with minimal impact on the qualitative characteristics of the food product Ezhilarasi et al, 2014;Rajam, Bharath Kumar, Prabhasankar, & Anandharamakrishnan, 2014). Only few studies have incorporated microcapsules into foods and analyzed their effect on food quality.…”
Section: Introductionmentioning
confidence: 99%
“…As stickiness limits the use of FOS as the wall material, a combination of high molecular weight whey protein with FOS overcomes the stickiness (Rajam et al, 2014;Rajam and Anandharamakrishnan, 2015). Matalanis et al (2011) reported that mixtures of food grade biopolymers, such as proteins and polysaccharides, which can be used to encapsulate and protect the bioactive components.…”
Section: Introductionmentioning
confidence: 99%